The Effect Of Work Motivation and Discipline On Teacher Performance at Public Junior High School 1 Lamongan - Masram Masram; Abdul Malik Sayyidur Rohman; Cuk Triono Singgih; Mu’ah Mu’ah (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2023)
The teacher is an agent of change who is the key to the success of education, so the success or failure of educational goals depends on the teacher's performance. Factors that influence teacher performance include work motivation and work discipline. Some teachers at Public Junior High School 1 Lamongan have less motivation and discipline, which needs improvement, impacting performance. This is reflected in late arrivals, fewer hours to work, and inappropriate use of uniforms. From these problems, the purpose of this study was to determine the effect of work motivation and discipline on teacher performance and the combined effect of work motivation and work discipline on teacher performance at Public Junior High School 1 Lamongan. The research method uses a quantitative approach with a correlational design. The population of this study was all teachers at Public Junior High School 1 Lamongan with a total of 59 teachers, and the sampling technique used the entire population (Census). Data analysis techniques using regression analysis techniques. The results of this study indicate work motivation and discipline have a significant effect on teacher performance, and work motivation and work discipline simultaneously have a significant effect on teacher performance at Public Junior High School 1 Lamongan.